Functional outcome evaluation of Neer’s two part and three part proximal humeral fractures treated by percutaneous K-wire fixation in a tertiary care hospital in North India: a prospective study of 21 patients - Spolia, Pankaj; Ghani, Abdul (International Journal of Research in Orthopaedics, 2021)
Background: The treatment of proximal humeral fractures is controversial. The advantages of percutaneous Kirschner’s wire (K-wire) fixation include preservation of periosteal blood supply, minimal blood loss, less soft tissue damage and shorter hospital stay. The aim of this study was to evaluate the 2 part and 3 part proximal humeral fractures in terms of functional outcome at final follow up. Methods: This was a prospective study of 21 patients aged 20 to 60 years with mean age of 44.2 years including two part and three part proximal humeral fractures based on Neer’s classification, treated by percutaneous K-wire fixation. Functional outcome was assessed by Constant-Murley score at 1 year follow up. Results: On the basis of Neer’s classification, 13 patients had 2 part fracture, 8 patients had 3 part fracture. Radiological union was achieved within 7 to 15.2 weeks, with an average of 11.6 weeks. The mean constant score at 1 year follow up was 78.2, range (42 to 96). In the present study, complications were seen in 8 (38.1%) patients. The results were in proximity with the existing literature. Conclusions: Percutaneous fixation is minimally invasive technique with preservation of periosteal blood supply, minimal blood loss, less soft tissue damage, surgery can be done under brachial plexus block, less chances of avascular necrosis, shorter hospital stay, no hardware in situ, thus no hardware symptoms, leaves no surgical scar and lowers the rate of complications.